2019
DOI: 10.1021/acs.molpharmaceut.9b00517
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of DEAE-Dx-Stabilized Cationic Bile-Based Vesicles over Conventional Vesicles for Enhanced Hepatic Delivery of Daclatasvir

Abstract: The purpose of our study was to improve the delivery of a direct-acting antiviral drug, daclatasvir, to the site of action, liver tissues, using physically and biologically stable cationic bile-based vesicles. Accordingly, cationic bile-based vesicles were prepared as pro-bile-based vesicles and diethylaminoethyl dextran (DEAE-Dx)-stabilized bile-based vesicles to increase their stability without negatively affecting their hepatic affinity. The prepared bile-based vesicles were characterized for particle size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Low PDI indicates that the BBV dispersion is homogeneous in nature. 60 The PDI was 0.17 ± 0.014, indicating good size homogeneity of the micellar solution.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Low PDI indicates that the BBV dispersion is homogeneous in nature. 60 The PDI was 0.17 ± 0.014, indicating good size homogeneity of the micellar solution.…”
Section: Resultsmentioning
confidence: 92%
“…The polydispersity index (PDI) is a measure of the distribution homogeneity of molecular size in a given sample. Low PDI indicates that the BBV dispersion is homogeneous in nature . The PDI was 0.17 ± 0.014, indicating good size homogeneity of the micellar solution.…”
Section: Resultsmentioning
confidence: 99%
“…Dual solvent systems were employed as mobile phases for assessment of the RLY. Acetone was utilized as a mobile phase for estimation of free 99m TcO 4 − percentage, whereas the 99m Tc-colloidal impurities were appraised through using 0.5 M NaOH [33].…”
Section: Determination Of the Radiolabeling Yield (Rly)mentioning
confidence: 99%
“…A standardized dose comprising similar injected quantity was concurrently counted and deemed as 100% activity. The uptake was described as % injected dose/g tissue (%ID/g) [33]. Muscles, bone, and blood were presumed to be 40, 10, and 7% of the whole-body weight, respectively.…”
Section: Animal Handling and Dissectionmentioning
confidence: 99%
“…Previously, it was shown that encapsulation of atorvastatin calcium (AC) in NPs ≥ 200 nm improved induced hyperlipidemia in rats with no adverse effects despite their lower bioavailability compared to Lipitor. These findings were attributed to increased liver uptake of larger AC-NPs resulting in apparent lower bioavailability in blood but better liver targeting unlike smaller particles AC-NPs < 100 nm which showed higher bioavailability due to preferential circulation in the plasma, mediocre liver targeting and increased toxicity ( [69][70][71].…”
Section: Liver-targeting Assessmentmentioning
confidence: 99%